Sistem Informasi Akuntansi Perhitungan Kredit Pemilikan Rumah Pada Bank Bjb Syariah Karawang Berbasis Vb.Net - Donny Apdian; Indaryono Indaryono; Rahmat Gunawan; Arif Maulana Yusuf (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
Bank BJB Syariah Karawang provides Loans and KPR. Loans and mortgages are Bank products in which the Bank provides a sum of money to lend to customers, with interest giving, but only a small proportion of them know the interest calculations or called Sharia-Buying when taking credit, whether it is a home loan or vehicle. The methodologi that the authors use in the writing of this thesis include the method of identification and system design. System identification includes organization identification, system running, and problem identification. While the design of the system includes design input output, DFD, ERD, data dictionary and database. Implementation activities in this company has been running well and also has been using computer-based systems, but the technology used is still a technology of the past. In doing the calculation of home loans based on sharia has also been using a computer system. As the authors observe, there are still problems that occur such as recording the margin calculation of each customer that takes a long time, so that will result in errors in the calculation of bank margin that has been established Based on the above matters, the authors argue that to overcome these problems, it is necessary to design and implement an integrated system among related functions in a system using Microsoft Visual Studio 2008 and its database Microsoft SQL Server 2005. With the implementation of the system it is expected that the input process and calculation of margin bank syaiah needed for the future can run smoothly and on time.